Genetic circuitry of Survival motor neuron, the gene underlying spinal muscular atrophy. - Sen, A.; Dimlich, D.N.; Guruharsha, K.G.; Kankel, M.W.; Hori, K.; Yokokura, T.; Brachat, S.; Richardson, D.; Loureiro, J.; Sivasankaran, R.; Curtis, D.; Davidow, L.S.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
The clinical severity of the neurodegenerative disorder spinal muscular atrophy (SMA) is dependent on the levels of functional Survival Motor Neuron (SMN) protein. Consequently, current strategies for developing treatments for SMA generally focus on augmenting SMN levels. To identify additional potential therapeutic avenues and achieve a greater understanding of SMN, we applied in vivo, in vitro, and in silico approaches to identify genetic and biochemical interactors of the Drosophila SMN homolog. We identified more than 300 candidate genes that alter an Smn-dependent phenotype in vivo. Integrating the results from our genetic screens, large-scale protein interaction studies, and bioinformatic analysis, we define a unique interactome for SMN that provides a knowledge base for a better understanding of SMA.